Bio-synthesis of citric acid from single and co-culture-based fermentation technology using agro-wastes. Issue 1 (January 2016) - Ali, Sohaib Rafaqat; Anwar, Zahid; Irshad, Muhammad; Mukhtar, Saima; Warraich, Nabeela Tariq
Abstract: Agro-based materials are primarily composed of complex polysaccharides that strengthen microbial growth for the production of industrially relevant value-added products. Therefore, in the present study, solid state fermentation (SSF) was carried out using agro-based waste materials (apple pomace, peanut shell and a mixture of both apple pomace and peanut shell with 50:50 ratio) as carriers/support for SSF to enhance citric acid production from single and co-culture consortia of Aspergillus ornatus and Alternaria alternata . During initial screening trial it was observed that growth media supplemented with apple pomace under SSF process of co-culture consortia presenting the preeminent 0.46 ± 0.42 mg/mL of citric acid. On partial optimization co-culture showed the maximum citric acid yield (2.644 ± 0.99 mg/mL) in the presence of arginine as a nutritional ingredient at 30 °C in an apple pomace based medium at 50% moisture content with pH of 5 and substrate concentration (25 g) after 48th of solid state fermentation. In conclusion, a suitable addition of fermentative substrate to the SSF medium increased fungal growth, sugar utilization and citric acid production when used in lower concentrations.